Cardiology secrets - Levine, Glenn N. (Philadelphia, PA : Elsevier, 2023)
Cardiology Secrets, 6th Edition, offers practical, up-to-date coverage of the full range of essential topics in this dynamic field. This highly regarded resource features the Secrets' popular question-and-answer format that also includes lists, tables, pearls, memory aids, and an easy-to-read style - making inquiry, reference, and review quick, easy, and enjoyable
Includes bibliographical references and index
Keywords: Cardiology -- Miscellanea; Heart -- Diseases; Heart Diseases; Diagnostic Techniques, Cardiovascular